Bunny's lessons - Ziefert, Harriet (Blue Apple Books, 2011)
A stuffed rabbit learns much from Charlie, his constant companion, including the meaning of the words "loud," "ouch," and "messy," but also about saying you are sorry and knowing you are loved.